A study of height and width of typical lumbar pedicles in relation to mechanical load - Amrish Tiwari; Shilpa Pandey; Deepak C. Naik (Universiti Kebangsaan Malaysia, 2015)
Background: Spinal instrumentation has been increasingly used to treat degenerative spinal disorders. Adequate anatomical knowledge of vertebral pedicles is necessary for proper instrumentation. Objectives: This study aimed at typical lumbar vertebrae to understand various measurements of pedicle. Materials and Methods: This study was conducted on 45 dry typical lumbar vertebrae obtained from Department of Anatomy Shyam Shah Medical College, Rewa, Madhya Pradesh. Pedicle vertical height (h) and width (w) were taken with the help of a sliding vernier caliper. Results: It was found that the height of the typical lumbar pedicle varied between 10 and 16.1 mm whereas the width varied between 4 and 19.6 mm. Conclusion: Steffee pedicle screw of 4 mm size is safe in typical lumbar vertebrae for spinal instrumentation.